Effect of various bacteriological media on the plaque morphology of Staphylococcus and Vibrio phages. Issue 4 (17th June 2019) - Ramesh, Nachimuthu; Archana, Loganathan; Madurantakam Royam, Madhav; Manohar, Prasanth; Eniyan, Kandasamy
Abstract : The influence of media composition on the life cycle of bacteriophages to exhibit diverse plaque morphology on various bacteriological media was investigated by a double agar overlay method. Both Staphylococcus aureus phage and Vibrio parahaemolyticus phage showed altered plaque morphology from small to large and from clear to turbid, in different culture media used for the double agar overlay method.